Peningkatan Pengetahuan dan Minat Berwirausaha Pada Industri Kreatif di Kecamatan Pemulutan Ogan Ilir - Edutivia Mardetini; Riswan Jaenudin; Siti Fatimah; Firmansyah F; Dian Eka Amrina (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Pemulutan is one of the sub-districts in Ogan Ilir region that has abundant natural potential in agriculture and livestock. The community has taken advantage of this potential but has not yet optimized its potential in the creative industries. Whereas there are many business sectors that can be developed in accordance with the potential of the region owned. The purpose of this dedication is to provide insight into the entrepreneurship of the creative industries for young generation and to increase participants' interest in entrepreneurship at the creative industries. This devotion is carried out in Ogan Ilir Pemulutan Sub-district, which is targeted by youth of cadets as many as 27 people. Model devotion used is the accompaniment with the method of delivering material about entrepreneurship in the creative industries. Evaluation is done through knowledge test and entrepreneurship interest questionnaire in creative industries. The results from participants' initial tests on entrepreneurial knowledge in the creative industries are average of 5.63, and average of 6.93 in the final test, and the increase of 0.28 with the low categories. The increase was accompanied by a very strong interest by participants to entrepreneurship in the creative industries by 82.13%. In conclusion, this dedication activity can provide basic knowledge and stimulate interest to youth for entrepreneurship in creative industries.